Ефективний вплив вправ CrossFit на рівень фізичної підготовленості алжирських старшокласників - Hamzaoui Hakim; Mime Mokhtar; Benchehida Abdelkader; Cherara Lalia (Lesya Ukrainka Volyn National University, 2021)
The aim of this study was to assess the effectiveness of a CrossFit exercises over a period of 8 weeks in a group of high school students during their physical education sessions at the school and to mitigate the deficits in fitness caused by COVID-19 prevention measures. Stuff and Research Methods. 94 students aged 16-17 years were randomly allocated into an included 46 students (2nd level: 12 male and 11 female students; 3rd level: 12 male and 11 female students) and 1 control group included 48 students (2nd level: 13 male 11 female students; 3rd level: 13 male and 12 female students of experimental group (EG) that performed the 8 weeks CrossFit. During the study, students in the control group (CG) were based only on the general physical education and sports program for high school students in secondary school. Physical fitness tests were done: lifting straight legs in height (number times); running on the spot with an intensity of 70 % of the maximum to severe fatigue (c); shuttle run 4× m (with); 60 m run (s) and cross twine (cm). Results of the Research. Our conducted research shows the positive influence of the CrossFit. There are a considering changes, development of the maximum dynamic force endurance, speed abilities, flexibility and mobility in the hip joints of the main groups, In the age aspect, there is mainly the improvement in results with age, both in the main and control groups (p>0,05). Conclusions. The study achieved a significant improvement in the physical condition of the students, also allows to talk about the effectiveness of training, built on the basis of a motivated choice of the target CrossFit high school program.